ANTESEDEN YANG MEMENGARUHI LOYALTY ONLINE PURCHASE INTENTION PADA KONSUMEN APLIKASI SEPHORA DI JAKARTA - KEISHA NABEELA; ANDHALIA LIZA MARIE (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
The purpose of this study is to analyze and determine the influence of Hedonic Motivations of Adventure (HMOA), Access to Online Information (ATOI), Online Trust (OT), and Online Prices (OP) on Loyalty Online Purchase Intention (LOPI) among users of the Sephora Application in Jakarta. The object used in this research is Sephora Application. The sample was selected using purposive sampling, resulting in 200 repondents who were buyers and users of the Sephora Application on smartphones. The method applied in this study is Structural Equation Modeling (SEM) using Partial Least Square (PLS) with the SMART PLS 4.0 software. The result obtained in this study reveal that Hedonic Motivation of Adventure variable has an influence on Loyalty Online Purchase Intention. The Access to Online Information variable has an influence on Loyalty Online Purchase Intention and Online Trust. The Online Trust variable has an influence on Loyalty Online Purchase Intention. The Online Prices variable has an influence on Hedonic Motivations of Adventure and Loyalty Online Purchase Intention among users of the Sephora Application in Jakarta.